FIFTY YEARS OF WATERSHED DEVELOPMENT IN INDIA AN OVERALL PICTURE OF WATERSHED MANAGEMENT - Bali, J.S. (Journal of Soil and Water Conservation, 2022)
Watershed management is not a subject: it is a strategy. It is a strategy of Area Development. Only, the area is a Watershed. The subject is Soil & Water conservation.